The influence of mycorrhization with Tuber melanosporum in the afforestation of a Mediterranean site with Quercus ilex and Quercus faginea (Forest Ecology and Management, 2006)
A Holm oak (Quercus ilex L.) and Lusitanian oak (Quercus faginea) stand establishment, mycorrhizated with black trufﬂe (Tuber melanosporum Vitt.), situated in the north of Alicante, south-eastern Spain, was analyzed during the second year of plantation. The mycorrhization improved seedling growth, especially that of the shoots, encouraged water uptake of the seedlings during the summer drought, and improved total phosphorus absorption. Tuber melanosporum was found to colonize the roots of the seedlings very successfully